Effect of Planting Date and Zinc Sulfate on Phenology, Growth Indices and Grain Yield of Lallemantiaiberica (M.B.) Fischer & Meyer - Mina Rostami; Farid Shekari; Kamran Afsahi; Majid Khiyavi (Ikufīziyuluzhī-i Giyāhān-i Zirā̒ī)
The production of oilseeds, edible leaves, and secondary metabolites of dragon's head makes it an important food, forage, and medicinal plant. Choosing a proper planting date and plant nutrition can make a significant effecton crop plantsgrowth, quality and yield.The effects of planting date (16 March, 14 April, and 13 May 2019) and foliar application of zinc sulfate (zero as control, 2 and 4 g.L-1) on growth indices and seed yield of dragon's head was evaluated under a field experiment.Delayed planting date reduced the days to flowering, days to seed ripening, plant height, leaf area index (LAI), crop growth rate (CGR), relative growth rate (RGR) and grain yield, and yield components.In contrast, the use of zinc sulfate increased plant height, LAI, CGR and RGR. There was a correlation between plant height and number of branches and consequently there were more capsules per plant.The highest effect of zinc sulfate application on seed yield and yield components was observed in the first planting date and with delay in planting, the efficiency of zinc sulfate fertilizer application decreased. On the third planting date, zinc sulfate application had no significant effect on grain yield. As a result of late planting, fewer branches, fewer capsules per plant, and smaller seeds contributed to the yield reduction.It was found that early cultivation and application of zinc sulfate increased plant height, number of branches, number of capsules per plant, 1000-seed weight, and thus seed yield, by increasing the days to flowering, days to ripening, LAI, CGR, and RGR.